Perceived employment discrimination and its relation to job satisfaction and intention to turnover - Menişa, Özen (My University, 2006)
İŞ AYRIMCILIĞI ALGISI İLE İŞ DOYUMU VE İŞTEN AYRILMA NİYETİNİN İLİŞKİSİ Bu araştırma iş ayrımcılığını, çalışanların iş doyumunu ve işten ayrılma niyetlerini olumsuz etkileyen bir olay olarak ele almıştır. Somut olarak bu çalışma; işyerindeki ayrımcılık algısı, iş doyumu ve işten ayrılma niyeti arasındaki ilişkiyi incelemektedir. Bunun yanı sıra iş doyumunun; işyerinde ayrımcılık ve işten ayrılma niyeti arasındaki ilişkide ara değişken olarak işleyip işlemediğini araştırmaktadır. Çalışma, demografik özellikler ve ayrımcılık çeşitleri arasındaki ilişkileri de ele almaktadır. Araştırmaya, çeşitli alanlarda çalışan, farklı özelliklere sahip 229 kişi katılmıştır. Elde edilen sonuçlara göre; algılanan ayrımcılık çeşitleri ve iş doyumu arasında negatif bir bağlantı bulunmaktadır. Aynı zamanda iş doyumu ve işten ayrılma niyeti arasında negatif bir ilişki vardır. Bunların yani sıra, iş doyumu; iş ayrımcılığı algısı ve işten ayrılma niyeti arasındaki ilişkiyi de, araya giren değişken olarak etkilemektedir. Araştırma; bazı demografik özelliklerin ayrımcılık çeşitleriyle bağlantılı olduğunu da ortaya koymuştur. Araştırma bulguları gösteriyor ki; ayrımcılığın kaldırılması ile, şirketlerde iş memnuniyetinin artması ve dolayısıyla çalışanların elde tutulma kapasitesinin büyümesi sağlanabilir. Ayrımcılığa maruz kalan gruplar hakkında bilinçlendirmenin geliştirilerek, şirketlerde moral, maddi ve zaman kayıplarının azaltılması sağlanabilir.

PERCEIVED EMPLOYMENT DISCRIMINATION AND ITS RELATION TO JOB SATISFACTION AND TURNOVER INTENTION This study investigated discrimination in the workplace as a phenomenon negatively affecting employees’ satisfaction with job and finally, leading to turnover. More concretely, it analysed the relationship between perceived employment discrimination, job satisfaction, and intention to turnover. It also tried to find out whether job satisfaction intervenes in the relation between perceived discrimination and turnover intention. Moreover, the relations between demographic characteristics and discrimination types were investigated. The data were collected directly or via electronic mail from 229 people working in diverse employment sectors. The findings of the research indicated that perceived discrimination had a direct and negative contribution on the job satisfaction of those feeling discriminated against, that job satisfaction had a direct and negative contribution on the intention to turnover of the employees, and that job satisfaction intervened in the relation between perceived discrimination and intention to turnover. Furthermore, demographic characteristics were found to influence the way people perceived discrimination. Research findings imply that reducing and eliminating discrimination might increase organizations’ capacity of preventing turnover through increasing job satisfaction. Also, awareness about groups who seem to suffer from discrimination may be developed. Thus, losses in terms of morale, finance, and time for the organization could be minimized.
Keywords: İş Ayrımcılığı; İş Doyumu; İşten Ayrılma